Sustained organic amendments utilization enhances ratoon crop growth and soil quality by enriching beneficial metabolites and suppressing pathogenic bacteria - Fallah, Nyumah; Pang, Ziqin; Lin, Zhaoli; Nyimbo, Witness Joseph; Lin, Wenxiong; Mbuya, Sylvain Ntambo; Ishimwe, Captoline; Zhang, Hua (Frontiers in Plant Science, 2023)
Organic soil amendments such as filter mud (FM) and biochar (BC) can potentially influence the abundance and composition of metabolites. However, our current understanding of the stimulatory effects of FM and BC's long-term impact on stress-regulating metabolites, such as abscisic acid (ABA), jasmonic acid (JA), melatonin, and phenyllactic acid (PLA), and these substrates regulatory effects on disease-causing bacteria in sugarcane ratooning field, which is susceptible to nutrients depletion, diseases, etc., remain poorly understood. Additionally, little is known about how the long-term interaction of these substrates and compounds influences sugarcane ratooning soil enzyme activities, nutrient cycling, and crop growth performance. To answer these questions, we adopted metabolomics tools combined with high-throughput sequencing to explore the stimulatory effects of the long-term addition of FM and BC on metabolites (e.g., PLA and abscisic aldehyde) and quantify these substrates’ regulatory effects on disease-causing bacteria, soil enzyme activities, nutrient cycling, and crop growth performance. The result revealed that ratoon crop weight, stem diameter, sugar content, as well as soil physico-chemical properties, including soil nitrate (NH3+-N), organic matter (OM), total nitrogen (TN), total carbon (TC), and β-glucosidase, marked a significant increase under the BC and FM-amended soils. Whereas soil available potassium (AK), NO3--N, cellulase activity, and phosphatase peaked under the BC-amended soil, primarily due to the enduring effects of these substrates and metabolites. Furthermore, BC and FM-amended soils enriched specific stress-regulating metabolites, including JA, melatonin, abscisic aldehyde, etc. The sustained effects of both BC and FM-amended soils suppressed disease-causing bacteria, eventually promoting ratooning soil growth conditions. A number of key bioactive compounds had distinct associations with several beneficial bacteria and soil physico-chemical properties. This study proves that long-term BC and FM application is one of the eco-friendly strategies to promote ratoon crop growth and soil quality through the enrichment of stress-regulating metabolites and the suppression of disease-causing bacteria.